Predictive value of neutrophil to lymphocyte ratio for clinical outcomes in liver cirrhosis: A systematic review and meta-analysis - Jingjing Lin; Mengna Huang; Lina Shen (PLoS ONE, 2025)
Background The neutrophil-to-lymphocyte ratio (NLR) is a simple yet potent marker that has been established as an independent predictor of mortality in patients with cirrhosis. However, consensus is lacking regarding its prognostic value for predicting mortality risk in these patients. Therefore, we conducted a meta-analysis to clarify its clinical significance. Methods We performed a literature search in PubMed, Web of Science, Cochrane Library, and Embase for studies published from database inception until January 1, 2025. Studies focusing on the diagnosis of cirrhosis were included, while those involving children and neonates were excluded. Odds ratio (OR) and its 95% confidence interval (CI) were calculated using the random-effects model. Sensitivity analysis was conducted to assess heterogeneity, subgroup analysis to explore sources of heterogeneity, and Egger’s test to evaluate publication bias. All analyses were performed using Review Manager (v5.4.1) and Stata (v15.0). Results A total of 18 studies involving 7,714 patients were included. Significant associations were obserced between the NLR and mortality (OR = 1.16, 95% CI: 1.10–1.22; P < 0.00001), infection (OR = 0.67, 95% CI: 0.37–0.96; P < 0.0001), and ascites (OR = 2.03, 95% CI: 1.43–2.88; P < 0.0001). However, no signficant correlation was found between the NLR and hepatic encephalopathy (OR = 1.33, 95% CI: 0.89–2.00; P = 0.16). Subgroup analysis indicated that heterogeneity was partly attributable to variations in NLR cut-off values. Egger’s test revealed significant publication bias only for mortality. Conclusion NLR is a well-validated prognostic biomarker for mortality, infection, and ascites in patients with cirrhosis. Systematic review registration PROSPERO, identifier CRD420251031417.